Major Macroeconomic Variables, Monetary Policy, and the Determination of the Neutral Interest Rate in Brazil - Melo, Marcelo Miranda de; Gomes, José Weligton Félix (Archives of Business Research, 2022)
This research used ARDL methodology to explore relevant macroeconomic variables influence on the Brazilian neutral interest rate. As a non-observable variable, we used this approach to identify the determinants of neutral interest rate in the Brazilian economy not only in the short term but also in the long run. Our descriptive analysis highlights that the trend of the real interest rate in Brazil has also been decreasing in recent years. In this paper we attempt to identify which variables could have driven such a fall. We used monthly data from January/2003 to June/2021 and the macroeconomic variables investigated are described as follows: neutral real interest rate (NRI), inflation rate (INF), 3-month treasury bill rate (TB3MS), real exchange rate (EER), Economic Activity Index (IBC-Br). All data were collected from IBGE, IPEADATA and Central Bank of Brazil (BACEN). We achieve that the variables that positively influence the long-term real interest rate are the inflation rate followed by the global interest rate trajectory and the real exchange rate, respectively. On the other hand, economic growth according to its potential level has a negative and relevant impact on the real long-term interest rate.